1999
DOI: 10.4315/0362-028x-62.8.867
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium botulinum Spores and Toxin in Mascarpone Cheese and Other Milk Products

Abstract: A total of 1,017 mascarpone cheese samples, collected at retail, were analyzed for Clostridium botulinum spores and toxin, aerobic mesophilic spore counts, as well as pH, a(w) (water activity), and Eh (oxidation-reduction potential). In addition 260 samples from other dairy products were also analyzed for spores and botulinum toxin. Experiments were carried out on naturally and artificially contaminated mascarpone to investigate the influence of different temperature conditions on toxin production by C. botuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 0 publications
0
19
0
1
Order By: Relevance
“…We found that all nontypeable strains produced the same RAPD profile, which was distinguished from the profiles of the other strains, suggesting a strict genetic relationship between them. This finding was interesting since most of the nontypeable strains had been isolated from an outbreak of botulism due to contaminated mascarpone consumption and from different samples of mascarpone and other cheeses analyzed during that outbreak (12). In total, the 37 Italian C. botulinum strains yielded a few banding patterns with both PFGE and RAPD techniques; therefore, since they had been isolated in different places and years, a low genetic diversity among strains distributed in Italy can be deduced.…”
Section: Vol 70 2004mentioning
confidence: 88%
See 1 more Smart Citation
“…We found that all nontypeable strains produced the same RAPD profile, which was distinguished from the profiles of the other strains, suggesting a strict genetic relationship between them. This finding was interesting since most of the nontypeable strains had been isolated from an outbreak of botulism due to contaminated mascarpone consumption and from different samples of mascarpone and other cheeses analyzed during that outbreak (12). In total, the 37 Italian C. botulinum strains yielded a few banding patterns with both PFGE and RAPD techniques; therefore, since they had been isolated in different places and years, a low genetic diversity among strains distributed in Italy can be deduced.…”
Section: Vol 70 2004mentioning
confidence: 88%
“…Thirty-seven strains were from the culture collection of the Istituto Superiore della Sanità (Italy's National Health Institute), Rome, Italy, including 17 clinical isolates representing all of the clinical isolates from type A botulism in Italy since 1993 and 20 food isolates. Seven of the clinical isolates were from patients involved in an outbreak of food-borne botulism in Italy caused by the consumption of contaminated "mascarpone" cheese (1); 18 of the food isolates were from mascarpone cheese samples and other cheese products analyzed during that outbreak (12). The remaining 20 strains, including reference strain 62A, had been kindly provided by C. L. Hatheway of the Botulism Laboratory of the Centers for Disease Control and Prevention, Atlanta, Ga.…”
Section: Methodsmentioning
confidence: 99%
“…In a third survey, C. botulinum was not isolated from 25 g portions of 90 samples of dry cereal and 100 samples of commercial baby formula (Kautter et al, 1982). It has been estimated that the contamination level of C. botulinum in milk is about 1 spore l À1 (Collins-Thompson & Wood, 1993), and Franciosa et al (1999) suggest that a sample size of at least 50 g is needed to give a realistic estimate of the number of organisms present. Based on the result presented here from the unopened can of infant formula feed, we have estimated that samples of .200 g are necessary for a 95 % chance of detecting a single C. botulinum.…”
Section: Analysis Of Foodsmentioning
confidence: 99%
“…Milk counts showed that numbers were generally under detection level (2040 spores L -1 ). Milk products, like cheese, may have contamination level around 10 spores g -1 cheese (Franciosa et al, 1999). Cheeses that may be contaminated are the same as the ones with butyric acid spores.…”
Section: Clostridium Botulinummentioning
confidence: 99%